Food order system for Nasi Kukus MyMama by using mobile application - Muhammad Redzuan, So’odi (2019)
Food delivery is a courier service in which a restaurant, store, or independent food delivery company delivers food to a customer. An order is typically made either through a restaurant or grocer's website or phone, or through a food ordering company. This document will explain in detail about the development of Food Order System for Nasi Kukus MyMama. This project was developed for android-based devices that support android application package file format. The development of this project is carried out by using java programming. This project target customers that live near Nasi Kukus MyMama Restaurants located in Kuantan and Gambang area. This project was developed under Rapid Application Development (RAD) methodology. RAD focuses on collecting customer requirements, early testing of the prototypes by the customer using iterative concept, reuse of the existing prototypes (components), continuous integration and rapid delivery.